2012
DOI: 10.1071/bt11174
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology of the Myrtaceae. Part 1: tribes Eucalypteae, Lophostemoneae, Syncarpieae, Xanthostemoneae and subfamily Psiloxyloideae

Abstract: A family-wide palynological study of Myrtaceae was conducted using scanning electron microscopy (SEM) and light microscopy (LM). In this part of the study, the pollen morphology of 18 genera and 150 species from the Myrtaceae tribes of subfamily Myrtoideae, Eucalypteae, Lophostemoneae, Syncarpieae, Xanthostemoneae and subfamily Psiloxyloideae are presented. It was found that the most commonly observed pollen in these groups was parasyncolpate with a rugulate exine, whereas some species possessed an apocolpial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Myrtaceidites lipsis does not appear until the late Miocene and possesses the diagnostic characteristics of pollen produced by extant Eucalyptus spathulata Hook. (e.g., Thornhill and Macphail, 2012; Thornhill et al, 2012b). In New Zealand, pollen that may represent Eucalyptus is reported to occur in lower Miocene to lower Pleistocene sediments (Mildenhall, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Myrtaceidites lipsis does not appear until the late Miocene and possesses the diagnostic characteristics of pollen produced by extant Eucalyptus spathulata Hook. (e.g., Thornhill and Macphail, 2012; Thornhill et al, 2012b). In New Zealand, pollen that may represent Eucalyptus is reported to occur in lower Miocene to lower Pleistocene sediments (Mildenhall, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different eucalypt (i.e., Myrtaceae) species typically have pollen that cannot be distinguished with palynological methods because of their parasyncolpate and tricolpate shape and similar size (Thornhill et al. ), rendering assessment by color or costly DNA meta‐barcoding a more appropriate approach for comparative analyses. We additionally assessed pollen diversity by (1) palynological analysis via pollen microscopy (see Appendix ) and (2) pollen DNA meta‐barcoding (Appendix ; Keller et al.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that long-stemmed, species-poor lineages such as Arillastrum are uninformative for studying biogeography because they have probably experienced a substantial amount of extinction during their evolutionary history and could have arrived in their present location at any time over a long period (Crisp et al, 2011b;Grandcolas et al, 2008). Because there are no known unequivocal macrofossils of Arillastrum, and because extant Arillastrum pollen is not distinctive enough to be recognized in the Cenozoic fossil record (Thornhill and Macphail, 2012;Thornhill et al, 2012a), the question of whether Arillastrum is endemic to New Caledonia as a result of vicariance will be almost impossible to answer with confidence.Arillastrum is not the only example in Myrtaceae of a geographically restricted, species-poor clade that has a sister relationship with a widespread, species-rich group. Others include Psiloxyloideae (4 spp.)…”
Section: The Presence Of Myrtaceae On Continental Islandsmentioning
confidence: 99%
“…To calibrate the relaxed molecular clock, we used eight fossil pollen and four macrofossil calibrations that had been identified as optimal on the basis of phylogenetic placement (Thornhill and Crisp, 2012;Thornhill et al, 2012d), extant pollen morphology (Thornhill et al, 2012a(Thornhill et al, , 2012b(Thornhill et al, , 2012c and oldest fossil age (Thornhill and Macphail, 2012) (Supplementary Table S2). The root node of the tree representing the divergence between Myrtaceae and its sister family Vochysiaceae was calibrated using a crown age estimate of Myrtales obtained by Wang et al (2009), who conducted a thorough molecular dating analysis of the rosid clade.…”
Section: Fossil Calibrationsmentioning
confidence: 99%